The tombs of Atuan - Le Guin, Ursula K., 1929-; Garraty, Gail (New York : Bantam, 1984)
Arha's isolated existence as high priestess in the tombs of Atuan is jarred by a thief who seeks a special treasure.
Elem. School Library Collection.
Newbery Medal/Honor.
Notable/Best Books (A.L.A.).
Booklist, January 2006.
Elem. School Library Collection, June 2000.
Kirkus Review, January 2009.
Keywords: Fantasy; Magic -- Fiction; Wizards -- Fiction; Magic -- Fiction; Wizards -- Fiction; Fantastic fiction